1997
DOI: 10.1002/j.1550-8528.1997.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometrics Do Not Influence Dual X‐ray Absorptiometry (DXA) Measurement of Fat in Normal to Obese Adults: A Comparison with In Vivo Neutron Activation Analysis (IVNA)

Abstract: MARCUS, MATTHEW A, JACK WANG, JOHN C THORNTON, R U M 1 MA, SANTIAGO BURASTERO, RICHARD N PIERSON, JR. Anthropometrics do not influence dual X-ray absorptiometry (DXA) measurement of fat in normal to obese adults: A comparison with in vivo neutron activation analysis (IVNA). Obes. Res. 1997;5: 122-130. Dual-energy X-ray absorptiometry (DXA) is now a commonly used method for the determination of bone mineral status and body composition in humans. The purposes of this study were to compare fat mass by in vivo neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Ca DXA overestimates TBCa by about 300 g when compared to Ca IVNA . This overestimation was also found by others in nonobese populations (44 g for Pierson, 3 600 g for Marcus 9 ). As previously described, the measurements of TBCa by the two in vivo methods were highly correlated (R = 0.937).…”
Section: Discussionsupporting
confidence: 85%
“…Ca DXA overestimates TBCa by about 300 g when compared to Ca IVNA . This overestimation was also found by others in nonobese populations (44 g for Pierson, 3 600 g for Marcus 9 ). As previously described, the measurements of TBCa by the two in vivo methods were highly correlated (R = 0.937).…”
Section: Discussionsupporting
confidence: 85%
“…Normal BP values were defined according to those adopted for the definition of the MS. 37 Total and regional body composition was determined by DXA, using a fan beam Hologic QDR 4500 A absorptiometer (Hologic Europe, Zaventem, Belgium). 43,44 Total and regional (trunk, arms, and legs) body composition was evaluated to assess absolute (grams) and percent fat mass (FM). For the estimation of precision, duplicate scans were obtained on the same day for 10 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is possible that any initial error in accuracy and subsequent DXA calibration was reproduced in newer generations of DXA instruments. Three recent studies using two different DGNA systems have reported calcium results lower than previous findings, which if divided by the BMC measured by DXA, yields 29-31% [5,35,36]. This finding prompted the current study, in which chemical analysis, DXA and DGNA were all utilized to measure the same cadaver bone.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, any initial error in DGNA accuracy presumably was reproduced in newer generations of DXA instruments. In fact, three recent studies using the upgraded DGNA systems have reported calcium content as 29-31% of the BMC measured by DXA [5,35,36].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation